Stable SrCo0.7Fe0.2Zr0.1O3-δ cathode material for proton conducting solid oxide fuel cell reactors. (12th April 2018) - Shao, Lin; Si, Fengzhan; Fu, Xian-Zhu; Luo, Jing-Li
Abstract: SrCo0.7 Fe0.2 Zr0.1 O3-δ (SCFZ) perovskite is prepared using a combustion method. SCFZ exhibits high stability while SrCo0.8 Fe0.2 O3-δ without Zr doping decomposes in CO2 and H2 O- containing atmosphere at elevated temperature. SCFZ also displays excellent chemical compatibility with BaCe0.7 Y0.2 Zr0.1 O3-δ (BCYZ) proton conductor. A ceramic membrane fuel cell reactor is assembled with SCFZ + BCYZ composite cathode, porous Pt anode and BCYZ electrolyte. High selective ethylene and electrical energy are co-generated from ethane in the proton conducting solid oxide fuel cell reactor. Highlights: SrCo0.7 Fe0.2 Zr0.1 O3-δ displays excellent chemical stability as the cathode in PC-SOFC reactor. 21% ethylene yield with 91% selectivity at 700 °C, cogenerate the peak power density of 129 mW cm −2 . Environmentally friendly, without carbon dioxide emission.